Impact of side-chain extension on physical and electronic properties of cross-conjugated Poly(thienylene vinylene)s (PTVs). (12th March 2019) - Zhang, Zhen; Zong, Xupeng; Sun, Zaicheng; Qin, Yang
Abstract: Poly(thienylene vinylene)s (PTVs) are close analogs to the extensively studied polythiophenes and the insertion of one double bond between every two thiophene units along the main-chain of PTV backbone eliminates steric repulsion and potentially allows installment of conjugated side-chains without significantly distorting the main-chain planarity, offering a facile way of fine-tuning the polymer electronic properties through main-chain/side-chain cross-conjugation. We describe here a new methodology that combines acyclic diene metathesis and post-polymerization modification methods for the access of a series of cross-conjugated PTVs bearing aromatic side-chains connected to the main-chains through alkyne spacers. Compared with unfunctionalized PTVs, these cross-conjugated PTVs showed broader absorption ranges, reduced bandgaps, and rarely observed fluorescence. Organic solar cells employing the cross-conjugated PTVs displayed up to double the efficiency improvement over those employing pristine PTVs. For the first time, these PTVs were applied as sensitizers in composites with g-C3 N4 for photocatalytic hydrogen production. It was found that the relative energy level positions between the polymers and g-C3 N4 and polymer crystallinity likely played decisive roles in determining the hydrogen production efficiencies, which gave us useful guidelines on future optimization of polymer structures and selection of photocatalytic systems. Graphical abstract: Image 1 Highlights: Cross-conjugated poly(thienylene vinylene) (PTV) polymers. Main-chain to side-chain charge transfer interactions. Triple bond spacers eliminate main-chain side-chain steric hindrance.